Low Birth Weight Prevalence in Children Diagnosed with Neurodevelopmental Disorders in Dubai - Faisal A. Nawaz MBBS (cand.); Meshal A. Sultan MBBS, FRCPC (SAGE Publishing, 2021)
The aim of this study is to evaluate the prevalence of low birth weight and other perinatal risk factors in children diagnosed with neurodevelopmental disorders. This is one of the first studies in the Arabian Gulf region focused on the contribution of these factors toward the development of various disorders such as attention-deficit/hyperactivity disorder, autism spectrum disorder, and other mental disorders. This descriptive study was based on qualitative data analysis. We reviewed retrospective information from the electronic medical records of 692 patients in Dubai, United Arab Emirates. The prevalence of low birth weight in children with mental disorders was significantly higher as compared to the general population (16% vs 6% respectively). Furthermore, other risk factors, including high birth weight and preterm birth were noted to have a significant association with neurodevelopmental disorders. Future research on the impact of perinatal risk factors will contribute to advancement of early intervention guidelines.